Desempenho óptico de lentes intraoculares: nfluência das alterações de posicionamento e do poder dióptrico. - Bruno Lovaglio Cancado Trindade (2017)
Purpose: To analyze the magnitude of low and high order aberrations of different commercially available intraocular lenses (IOLs). To analyze the importance of these aberrations in the IOLs optical performance when they are perfectly centered as well as decentered or tilted. Materials and Method: Spherical and aspheric IOLs from 3 major global suppliers (Bausch & Lomb©, Alcon© e Abbott Medical Optics©) with optical powers of 15 diopter (D), 20 D and 25 D were analyzed. Two lenses of each power were used. A Hartmann-Schack based optical circuit was used to verify the induced aberrations and Zernike polynomials were used toreconstruct the detected wavefront. Intraocular performance was also simulated using a optical design software. Results: IOLs optical power measured were in accordance to the current international standards in all analyzed lenses. There was induction of astigmatism and coma with IOLdecentration and tilt. Aspheric lenses with negative spherical aberration, although having better optical performance when centered, had the highest performance compromise when decentered or tilted.Conclusions: Lens decentration and tilt produced aberrations that compromised image quality. Neutral" aspheric lenses had the best performance under these situations.